2003
DOI: 10.1149/1.1597883
|View full text |Cite
|
Sign up to set email alerts
|

Lithium Insertion into TiO[sub 2] Nanotube Prepared by the Hydrothermal Process

Abstract: A TiO 2 nanotube was prepared by a hydrothermal process. Transmission electron microscope tests showed that the products are uniform straight hollow tubes with the diam around 8 nm and the length over 300 nm. X-ray diffraction measurements indicate that the nanotubes crystallized in anatase TiO 2 . Cyclic voltammetry and galvanostatic charging and discharging tests showed that lithium-ion intercalation/deintercalation occured reversibly in the TiO 2 nanotube electrode, and a high capacity can be obtained. Elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
106
0
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(119 citation statements)
references
References 21 publications
10
106
0
3
Order By: Relevance
“…The nature of Li x TiO 2 intercalate is unclear (e.g., oxidative state of Ti of Li) but it is suggested that lithium atoms accommodate positions of ion-exchanged protons in titanate nanostructures or channels in TiO 2 -B nanofibers. [100,101] Recent studies [39,100,102] on the use of TiO 2 nanotubular anodes in a lithium battery demonstrate an initial 282 mA h g -1 discharge capacity at a specific current density of 0.24 mA g -1 . This corresponds to x = 0.98 in Equation 3, which is larger then the value of ca.…”
Section: Lithium Batteriesmentioning
confidence: 99%
“…The nature of Li x TiO 2 intercalate is unclear (e.g., oxidative state of Ti of Li) but it is suggested that lithium atoms accommodate positions of ion-exchanged protons in titanate nanostructures or channels in TiO 2 -B nanofibers. [100,101] Recent studies [39,100,102] on the use of TiO 2 nanotubular anodes in a lithium battery demonstrate an initial 282 mA h g -1 discharge capacity at a specific current density of 0.24 mA g -1 . This corresponds to x = 0.98 in Equation 3, which is larger then the value of ca.…”
Section: Lithium Batteriesmentioning
confidence: 99%
“…1 week or agitating the system to eliminate diffusion limitations. Layered anisotropic titanate nanostructures can be prepared from a broad range of TiO 2 sources [10][11][12] and using different compositions, bases [13][14][15], reaction times, temperatures and post-synthetic treatments. Changing the recipe allows fine-tuning the properties of the product mixture (e.g.…”
Section: Synthesis Of 1d Titanatesmentioning
confidence: 99%
“…24 TiO 2 nanotubes have been used as hydrogen sensors, 25 dye sensitized solar cells, 26 and have displayed photoluminescence properties. 27 Many inorganic layered nanotubes have shown the ability to intercalate lithium, hydrogen, and magnesium, [28][29][30][31][32][33][34][35][36][37] indicating potential as energy storage materials.…”
Section: Introductionmentioning
confidence: 99%